(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article analyzes the periphrasis used in proverbs and sayings. Periphrases of proverbs and popular expressions have no less cultural connotation than the units that served as the basis for paraphrasing. Cultural information encoded in such periphrases, is of great importance for lingua-culture, since, among other things, reflects the attitude of a modern Western speaker culture to traditional cultural values and stereotypes. Moreover, periphrases with cultural connotations reflect changes occurring in the mentality of a nation in relation about its cultural values.